Multifactor Prognostic Evaluation of Postoperative Craniopharyngiomas. Issue 1 (January 2021) - Yang, Fengyu; Liu, Wei; Cheng, Dekui; Zhang, Hongliang; Li, Ziji; Cao, Zhigang; Zhang, Jinwu; Lv, Bingke; Feng, Yugong; Li, Huanting
Abstract : Purpose: To evaluate various factors that could be associated with the postoperative prognosis of patients with craniopharyngiomas and provide evidence for the proper surgical course and optimal outcome assessments of craniopharyngiomas. Methods: We performed a retrospective study and reviewed 68 patients with craniopharyngiomas who received surgery from May 2013 to October 2018. The relationships between the disease prognosis and age, gender, onset symptoms, size of tumor, degree of calcification, consistency, QST classification, adhesion strength, and pathological types were analyzed. Results: There were no significant associations between the prognosis and age, gender, number of onset symptoms, and pathological types ( P > 0.05). The severity of onset symptoms, tumor diameter, and degree of calcification was significantly associated with the prognosis ( P < 0.05). There were significant different prognoses between patients with cystic and solid, mixed tumors ( P < 0.05). The prognosis of patients with T type tumors was different from that of patients with either Q or S type tumors ( P < 0.05). The prognoses of patients with either loose or tight type tumors were significantly different from those of patients with either invasive or fusion type tumors ( P < 0.05). Conclusion: Clinical and pathological variables, such as onset symptoms, size of tumor, degree of calcification, consistency, QST classification, and the degree of adhesion strength, were important factors in evaluating the prognosis of patients with craniopharyngiomas. Abstract : Supplemental Digital Content is available in the text